2022
DOI: 10.1101/2022.05.26.493539
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Virological characteristics of the novel SARS-CoV-2 Omicron variants including BA.2.12.1, BA.4 and BA.5

Abstract: After the global spread of SARS-CoV-2 Omicron BA.2 lineage, some BA.2-related variants that acquire mutations in the L452 residue of spike protein, such as BA.2.9.1 and BA.2.13 (L452M), BA.2.12.1 (L452Q), and BA.2.11, BA.4 and BA.5 (L452R), emerged in multiple countries. Our statistical analysis showed that the effective reproduction numbers of these L452R/M/Q-bearing BA.2-related Omicron variants are greater than that of the original BA.2. Neutralization experiments revealed that the immunity induced by BA.1 … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

17
168
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(185 citation statements)
references
References 58 publications
(261 reference statements)
17
168
0
Order By: Relevance
“…In our study, individuals infected with BA.4/BA.5 lineages did not have increased clinical severity compared to individuals infected with BA.1. Recent data from a study conducted in hamsters showed that BA.4/BA.5 was more pathogenic than BA.2 14 . However, in our study, this increased pathogenicity did not translate into clinical severity.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, individuals infected with BA.4/BA.5 lineages did not have increased clinical severity compared to individuals infected with BA.1. Recent data from a study conducted in hamsters showed that BA.4/BA.5 was more pathogenic than BA.2 14 . However, in our study, this increased pathogenicity did not translate into clinical severity.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study demonstrated that the L452R mutation enhances the infectivity of a pseudovirus carrying the BA.1 S protein in K18-hACE2 transgenic mice 11 . Notably, a recent paper (Kimura et al 5 ) reported that a recombinant chimeric virus possessing the BA.4 or BA.5 S gene in the background of a BA.2 strain is more pathogenic than the parental recombinant BA.2 virus in hamsters, suggesting that the S sequence differences between BA.2 and BA.4 or BA.5 are responsible for the difference in pathogenicity between these chimeric viruses; based on these data, Kimura et al concluded that BA.4 and BA.5 are more pathogenic than BA.2. However, in authentic viruses isolated from patients, the genomes of BA.2, BA.4, and BA.5 differ at locations other than the S gene.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that the L452R mutation increases the fusogenicity and infectivity of SARS-CoV-2 variants including Omicron 10,11 . Notably, a recent study reported that a recombinant chimeric virus possessing the BA.4/BA.5 S gene in the background of a BA.2 strain is more pathogenic than the parental recombinant BA.2 virus 5 . This nding suggests that the infectivity and pathogenicity of BA.4 and BA.5 may be higher than those of BA.1 and BA.2.…”
Section: Introductionmentioning
confidence: 99%
“…Others in contrast report that breakthrough infection with VOCs elicits crossreactive antibodies with the ability to neutralize Omicron [49,93,94]. Converging reports indicate that Omicron BA.1 breakthrough infection elicits antibodies with neutralizing activity against Omicron BA.1 and previous VOCs [27,48,[95][96][97] but poorly cross-neutralizing other Omicron sublineages [98]. In unvaccinated individuals, Omicron infections trigger poorly neutralizing antibodies against all VOCs [49,95,96].…”
Section: Introductionmentioning
confidence: 99%